Change Management in FMCGS in Lagos. A Study of Selected FMCGS in Lagos State - Ebenezer, Oluwaleke; Akhimie, Debbie; Lawal, Abdulraseed; Olonade, Olanrewaju (Acta Universitatis Danubius. Œconomica, 2023)
Fast Moving Consumer Goods Firms (FMCGs) are constantly under change in the effort to enhance their internal operations and become more competitive in the market. A change process is always challenging, and its success must consider multi-angled approaches, as it affects all stakeholders. The way changes are tackled is fundamental to the success and survivability of an enterprise. The main objective of this study is to examine change management in the FMCG industry using selected firms in Lagos State with specific goals to investigate how much employee involvement, employee training, resources, and leadership affect change management in Lagos. The study adopted a descriptive research design, and the study population consists of all the managerial staff of the 25 most rated companies in the FMCG industry in Lagos. The sample size was 100 respondents. The online survey was used, and the data collected were analyzed using factor analysis. The empirical results indicate that all selected key factors contribute towards achieving effective change management as hypothesized. The results of this work may benefit enterprise managers planning, executing, and assessing change processes, as proper considerations of the factors discussed throughout this work may increase the chances of the change process success, resulting in a better performing and competitive enterprise.